Motivation of general achievement and academic performance in Cuban dental students - Ibraín Enrique Corrales-Reyes; Oscar Javier Mamani-Benito; Edison Effer Apaza-Tarqui; Christian R. Mejia (Editorial Ciencias Médicas, 2022)
Introduction: When studying academic performance it is important to address the influencing factors in it, as well as the causes to which students attribute their successes or failures. Hence the need to have valid and reliable instruments for this purpose. Objective: Validate an attributional scale on the motivation of general achievement in relation to academic performance in Cuban students of Stomatology. Methods: An instrumental, cross-sectional and multicenter study included students from nine Cuban universities. From an instrument in Spanish, validated in Venezuelan students, exploratory and confirmatory factor analysis were performed. In addition, the internal consistency was calculated with Cronbach's alpha coefficient. Results: 1324 participants were included, of which 66.8% were women and the mean age was 21.2 ± 1.8 years. The statisticians KMO (0.918) and Bartlett (10112.063; gl = 153; p < 0.001) presented acceptable and significant results. The total variance explained by the 18 items distributed in four factors is adequate (60.6%). Robust analyses show how the factor structure is satisfactory. Significant relationships were found between all dimensions of the scale, which suggest the presence of adaptive and maladaptive attributional patterns. Conclusion: The scale is valid and reliable to identify causal attributions about overall academic performance in Cuban stomatology students.